EFFECTS OF LANDUSE AND LANDCOVER CHANGE ON FLOODING IN KANO METROPOLIS, KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
ABSTRACTThis paper looked at the change in land use land cover (LULC) of Kano metropolis from 2001 to 2012; projected to 2035 and thereby assessing the response of these different land covers to rainfall event using the Hydrologic Engineering Corps- Hydrologic Modelling System (HEC-HMS) model. The outcome of the LULC revealed that the built-up areas increased from 19.7% to 34.4% and then to 54.4% in 2001, 2012 and 2035, respectively. The discharge of Jakara basin indicated a rise from 2001, 2012 to 2035 in the order of 443, 585.2 to 609.7 cm3/sec respectively. However, that of Chalawa shows increase between 2001 and 2012 and a decrease in 2035 as a result of canalization within the basin. The paper recommended adherence to the city masterplan and construction of canals within each sub-drainage basin for proper conveyance of run-off discharge.
Keywords: Landuse and Landcover (LULC), HEC-HMS model, Chalawa basin, Jakara basin and sub- drainage basins